An Overview on The Pandemic Coronavirus Disease 2019 (COVID-19) Outbreak - Abdulla Hama Salih, Mariwan (Kurdistan Journal of Applied Research, 2020)
The current review covered most of the researches have been done since the new coronavirus found in Wuhan city of China at the end of December 2019 up to date by considering the most beneficial ones for our society. The severe acute respiratory syndrome coronavirus 2 or SARS-CoV-2 is a virus that potentially acts on the human respiratory system. It is first found in animal then transmitted into human. The virus can be transmitted between human to human via close contact or from the tiny droplet while coughing or sneezing. WHO characterized the situation by pandemic global concern because the virus spread over 200 territories and more than millions peoples were infected and over two hundred thousand people deceased as a result of COVID-19. At the moment nothing can stop the virus from spreading, neither vaccine nor medicines were found to stop the virus and secure life of people of the planet. The aim of the present review was to show the main feature of the SARS-CoV-2 and to find the common statements between the previously published studies on the output of their works. The other objective of this review was to encourage publics to treat the virus in safe way based on the discovery by researchers toward secure life of million peoples that could be infected by the 2019 new coronavirus. This review were summarized several researches about the SARS-CoV-2 since its appearance to present time May 2020. Several reports from WHO, CDC and FDA were included about spreading or the way of transmission, causes, prevention, diagnosis and risk factors of the COVID-19. The current review find the common statements about different aspects of the 2019 new coronavirus that could be help the new research to benefit from these statement for further investigations. This review showed that urgent steps for the current time to secure life of millions peoples is to quarantines people at home and governmental authorities have to take the responsibilities of this steps and to encourage people to stay at home and teach them the self-prevention is a better treatment for all humanities.